2018
DOI: 10.1080/19476337.2017.1415375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pomegranate seed oil and fermented juice polyphenols fraction in different solvents on copper-induced LDL oxidation

Abstract: Effects of pomegranate seed oils extracted with supercritical fluid or cold press methods (SFE-PSO and CP-PSO), unsaponifiable (N), and fermented juice polyphenols (W) fractions of pomegranate as well as olive oil and alpha-tocopherol, as pure or in different solvents were evaluated on preventing copper-induced LDL oxidation. The results showed addition of pure SFE-PSO, CP-PSO, N fractions, and olive oil had no significant effect on LDL oxidation. Also using various solvents did not help in the term of extendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Thus, before the oxidation assay, repeating dialysis may be necessary to remove these protectors and re-obtain LDL particles susceptible to the oxidative trigger used [116]. Resuspension of LDL particles for the assay is usually performed in either saline solution or PBS (pH 7.4) that is often subjected to oxygenation [60,121,122].…”
Section: Low-density Lipoprotein-based Assaysmentioning
confidence: 99%
“…Thus, before the oxidation assay, repeating dialysis may be necessary to remove these protectors and re-obtain LDL particles susceptible to the oxidative trigger used [116]. Resuspension of LDL particles for the assay is usually performed in either saline solution or PBS (pH 7.4) that is often subjected to oxygenation [60,121,122].…”
Section: Low-density Lipoprotein-based Assaysmentioning
confidence: 99%
“…Kaur et al (2006) found that the ethanol extract of pomegranate flowers contains a large amount of polyphenols and has a huge regenerating ability, which indicates a strong (81.6%) antioxidant capacity in the DPPH model system. Schubert et al (1999) and Faisi et al (2018) argue that the polyphenolic fraction of pomegranate juice can act as an anti-atherogenic supplement and natural preservative for meat and fatty foods by directly inhibiting the oxidation of LDL.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of factors such as enzymes, lipids, noncoding RNAs, and metabolites are involved in human disease. [44][45][46][47][48][49][50] One of these factors is endothelins, which exert various beneficial and detrimental physiological functions in paracrine and autocrine manner in a broad range of organs including blood vessels, brain, heart, kidney, and lung. 51 Endothelins have an increasing considerable role in development, as demonstrated by gene knockout experiments in mice.…”
Section: Physiological Function Of Etsmentioning
confidence: 99%